2018
DOI: 10.3390/f9030136
|View full text |Cite
|
Sign up to set email alerts
|

Role of Community and User Attributes in Collective Action: Case Study of Community-Based Forest Management in Nepal

Abstract: A growing literature on collective action focuses on exploring the conditions that might help or hinder groups to work collectively. In this paper, we focus on community-based forest management in the inner Terai region of Nepal and explore the role of community and user attributes such as group size, social heterogeneities, forest user' perception on forests, and affiliation to the user group, in the collective action of managing community forests. Household surveys were carried out with 180 households across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 90 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…They are the community who live in close proximity to the forests, and can manage the forest effectively (Brosius et al, 1998). The users form the community forest user groups who collectively engage in the management of forest, making them key actors in the functioning of community forests (Negi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They are the community who live in close proximity to the forests, and can manage the forest effectively (Brosius et al, 1998). The users form the community forest user groups who collectively engage in the management of forest, making them key actors in the functioning of community forests (Negi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, these broad social and ecological objectives do not always align, and there are diverse motivations for integrating biodiversity conservation, or the maintenance of habitats and biodiversity, and procedural social equity, which deals with fairness of process and involves inclusion, representation, and participation of individuals and groups in decision making (McDermott et al 2013, Law et al 2018. There are both practical and ethical rationales at play: including the utilitarian notion that procedural equity allows for diverse interests and values to be represented and defended (Gustavsson et al 2014), and the normative notion that participants should feel they've been consulted, allowed a voice, and had the freedom to contribute McDonough 2001, Martin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have focused on group size, but the effect of group size is still debated because the findings of previous studies are often inconsistent. For example, one study showed that cooperation was difficult to achieve for large groups involved in CF activities [71]. However, studies from Nepal and India found that larger forest groups tended to be more successful because more people were involved in monitoring and management activities [60,72].…”
Section: Group Sizementioning
confidence: 99%